A5.10 Increases in serum cholesterol with baricitinib treatment are associated with favourable changes in apolipoprotein content and with improvement in DAS28-CRP in patients with rheumatoid arthritis. (13th February 2015) - Kremer, J; Genovese, MC; Keystone, E; Taylor, P; Zuckerman, SH; Schlichting, DE; Nantz, E; Beattie, SD; Macias, WL
Abstract : Treatment with baricitinib (bari), an oral inhibitor of JAK1/JAK2, demonstrated improvements in signs and symptoms of RA through 52 wks in a Phase 2b study, 1 and also in dose- and time-dependent changes in serum lipids, LDL particle size and HDL and VLDL particle numbers. 2 Increases in HDL, but not LDL cholesterol, correlated with decreases in CRP at Wk 12. Changes in serum cholesterol, in apolipoprotein content of LDL, VLDL, and HDL particles were evaluated. Patients (pts) with RA were randomised to QD doses of placebo (PBO) (n = 98) or bari 1 mg (n = 49), 2 mg (n = 52), 4 mg (n = 52), or 8 mg (n = 50) for 12 wks. Pts assigned to 2-, 4-, or 8-mg bari continued blinded treatment for an additional 12 wks. Serum samples were collected through 52 wks for conventional lipid determinations (total cholesterol, LDL, HDL, and triglycerides). Apolipoprotein content was assessed at Wks 4 and 12 for PBO, 4-, and 8-mg bari groups. Pts treated with bari through 52 wks maintained a stable cholesterol and triglyceride profile with no further changes beyond Wks 12 and 24. Increases in apolipoprotein A-I, apolipoprotein B, and total apolipoprotein CIII were observed with 4- and 8-mg bari with no increase in LDL-associated apolipoprotein CIII. Bari treatment also demonstrated a significant reduction in HDL-associated SAA at the 4- and 8-mg doses compared to PBO while a significant reduction in Lp (a) was observed only in the 8-mg bari group (all p < 0.05). These changes in apolipoproteins coincided with the increases in serum lipids apparent by Wk 4. In pts treated across all doses of bari, a significant correlation was observed between change in HDL cholesterol and absolute DAS28-CRP score at Wk 12 (r = -0.33, p < 0.001) as well as the change from baseline to Wk 12 in the DAS28-CRP (r = -0.29, p < 0.001). Specifically, pts achieving DAS28-CRP <2.6 and larger decreases in DAS28-CRP demonstrated larger increases in HDL cholesterol. No significant correlations were observed in the PBO arm between HDL and disease activity measures and not between disease activity and total cholesterol or LDL levels in the bari arms. In addition to increases in serum cholesterol and lipoprotein particle number (HDL and VLDL) and size (LDL), there were changes in apolipoprotein content of these particles in pts treated with bari. The increase in HDL cholesterol with bari treatment correlated with an improvement in DAS28-CRP. References: Taylor P, Genovese MC, Keystone E, et al . Ann Rheum Dis 2013; 72 :A65–A66. Kremer J, Genovese M, Keystone E, et al . Baricitinib effects on serum cholesterol and circulating lipid particles in a Phase 2b study in patients with rheumatoid arthritis [abstract]. Ann Rheum Dis 2013; 72 (Suppl 3):241.